THE RELATIONSHIP OF PRINCIPAL LEADERSHIP AND ORGANIZATIONAL CLIMATE ON MOTIVATION AND PERFORMANCE OF TEACHER IN PRIMARY SCHOOL - Ferdiana, Rita; Suriansyah, Ahmad; Suhaimi (Journal of K6, Education and Management, 2019)
School is an institution where the educational process follows a complex and dynamic system. This study aimed to describe and analyze the effectiveness of the headmaster's leadership and organizational climate on achievement motivation and performance of teachers in the school setting. This research was correlational research using path analysis with 139 teachers as a sample and the data obtained was analyzed through the use of multiple regression methods. The results showed the effectiveness of the headmaster's leadership; organizational climate and teacher achievement motivation were included in the moderate category; while the teacher's performance was in a good category.